The Importance of Manuscripts and A Short Evaluation of the Status of Officially Unregistered Manuscripts - (:unkn) unknown (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2015)
The inscript that was discovered by the Sumerians has been the most effective tool in developing the science and technology and in the construction of civilization. Therefore, writing materials are important because they carry information, culture and experience. Writing materials include the manuscripts. In this situation, it is important to publish and serve these manuscripts to the world of science, containing lots of information and not having published yet On the other hand, our country is among the few countries in terms of manuscripts with rich collections. Also there are many manuscripts that are owned by civilians and unregistered with the state office. Thus it is important to ascertain and publish these works in many aspects not by the scientists educated by other countries, but the scientists of our country.
Keywords: Discovery of Inscription; Manuscripts; Science; Culture; New Generation; Citizens; Verification (Ascertain); Publications